הרטוריקה העברית - מלמד אברהם (מכאן, 2020)
This article explores the evolution of Hebrew and Jewish rhetoric, from Biblical literature to modern times. the Hebrew Bible contains specific rhetorical modes, but does not treat them from a theoretical perspective. Rabbinic literature on the other hand, was influenced by Greek-Hellenistic rhetoricc. The first theoretical discussions of rhetoric appeared in medieval Jewish thought - both the Muslim and Christian cultural environments, influenced by the Arabic translations and commentaries on Aristotelian rhetoric. This culminated with the Hebrew translation of Averroes’ commentary on Aristotle’s Rhetoric. Rhetoric became popular in humanistic circles of the Italian Renaissance, which was influenced by Roman rhetoric - the writings of Cicero and Quintilian - in addition to the old Aristotelian tradition. The influence of new humanistic rhetorical sensitivities in manifesst in Nofet Zufim, composed by Judah Messer Leon in the late 15th century. Later Jewish rthetorical discussion was influenced by Baroque tendencies, such as Leson Limudim by Ramhal. The main Hebrew rhetorical treatises were first published or republished in the 19th century, during the Jewish Enlightenment. Rhetoric, however, went out of fashion in contemporary Israeli culture. The medieval Hebrew term for rhetoric, halatza, means ’a joke’ in contemporary Hebrew.